(untitled) (Journal of the College of Education for Women, 2019)
The energy consider generally and specifically the petroleum energyfrom the prior requirement of the population and nations, and the basics of thesurvival of mankind and all the challenges for the sake of continuum, sowithout this energy the life of ankind being varied, so far the life is still as afact on the planet earth, and suppose the life may continue as the willing ofAllah ,that the events and the standards and the degree of development is stillas it is, in another word no any technical developments and no anyentertainment no transportation and also there is no demographic dominationfor the whole lands belonging to Allah, certainly no way to talk more on whatwe and the others knew, what is the great impact on our life and for thefuture of our coming generation and on the technical developments thatcharged our continuum and the lifestyle on various fields. The greediness isincreased and the desire is overcoming to control on populations meantimethese superpower countries is already succeeded by means of making use ofthis energy and ruled on the third world countries that is also ruled by theirleaders to punish their fellowships, and at the same time they obey and followthe orders that submits all the wicked for humankind and be slave tomurderers, under the consideration of no choices. So the best and the worsebeing together till the Holly Koran split the concepts and the peoples followthe philosophy and obey the instruction and show all the commitment towardthe standards which are full of wisdoms, for this reason or another they couldestablish and develop their nations and promote their conditions toward thebest. What is concerning to our self that in spite of all advantages andbenefits submitted from Allah that provides us with various kinds of energyresources , we went to follow the devil, and to destruct our society we havebeen in touch with the murderers, criminals and saw how the infrastructuresis completely damaged meanwhile the holly Koran is among us introduce allthe benefits and all the advantages and reminding us that not even the oil andgas is a available for us but all kind of energies like (solar, waters and thewinds), and different kinds of minerals like (sulfur, phosphate uranium, iron,copper, aluminum, limestone, clay minerals and salt) and so on. Thesebenefits are provided to Mankind in order to make use of it and to let thebelievers to be grateful, so this Surat in Koran is to explain and show thegreatness of the creator and how to open horizon for better life for humankind.